IMPLEMENTASI INOVASI PEMBELAJARAN JARIMATIKA SEBAGAI UPAYA PENINGKATAN KOMPETENSI NUMERASI SISWA - Dina Hairun Nissa; Eva Dianawati Wasliman; Sri Handayani (STKIP Subang, 2026)
Rapid developments have led to challenges in various areas of life, one of which is education. In this case, numeracy literacy is the aspect most highlighted by the Indonesian people because it is considered the most difficult challenge that must be resolved immediately. The purpose of this study was to determine the extent to which the application of the Jarimatika method can improve the numeracy competence of elementary school students, particularly in solving multiplication operations. This study adopts a descriptive qualitative approach with the aim of describing in depth the process of implementing the Jarimatika learning innovation in improving the numeracy competence of elementary school students. A qualitative approach was chosen because it allows researchers to obtain natural, contextual, and meaningful data through direct interaction with the research subjects. The results showed that the implementation of the Jarimatika learning innovation at SDN Nagrak 2 had a positive impact on improving students' numeracy skills. This method was effective in encouraging enjoyable learning activities and improving understanding of mathematical concepts. This study is expected to contribute to the development of more innovative and effective mathematics teaching methods. Based on the results of the study, it can be concluded that the implementation of the Jarimatika learning innovation in improving the numeracy skills of elementary school students is effective in improving the numeracy skills of elementary school students, especially in multiplication operations. Keywords: Educational innovation, jarimatika, numeracy skills, elementary school.